Clinicopathological characteristics and prognosis of resected cases of carcinoid tumors of the lung. Issue 6 (6th September 2016) - Yang, Zhi; Wang, Zitong; Duan, Yong; Xu, Shaofa
Abstract : Background: Lung carcinoid tumors are rare, low‐grade, malignant neoplasms with some unclear features. The aim of this study was to analyze clinicopathological features and long‐term survival in patients with primary lung carcinoid tumors. Methods: Patients who underwent surgery in our clinic and were diagnosed with carcinoid tumors, between August 1997 and July 2012, were included in the study. Patient characteristics and clinicopathological factors were retrospectively evaluated. Results: Bronchial carcinoids comprised only 1.0% of lung cancer cases treated by resection. They are classified into two distinct categories: typical carcinoid (TC) and atypical carcinoid (AC) tumors. AC tumors occurred more frequently in younger patients and in smokers, and had a poorer prognosis than TC tumors. Overall three and five‐year survival rates for TC and AC were 92.6% and 81.1%, respectively. Univariate analysis showed that tumor size ( P = 0.012) and histological type ( P = 0.013) are prognostic factors. Multivariate analysis revealed that only tumor size ( P = 0.044) was an independent prognostic factor. Conclusions: The prognosis for bronchial carcinoid tumors was better than other types of lung cancer and TC was significantly better than AC. Radical lymph node dissection was the best treatment, with complete removal of the tumor. Tumor size was an independent prognostic factor for bronchial carcinoid tumors.